Cinema e Segunda Guerra Mundial : análise da divulgação dos filmes antinazistas norte-americanos nos jornais de Sergipe (1942-1945) - Andrade, Liliane Costa (2019)
This academic work analyses how American Anti-Nazi movies produced during World War II (1939-1945) were announced on newspapers of Sergipe between the years of 1942 e 1945. This period comprehends the moment in which these Hollywood films were exhibited in Brazil, a consequence of the cut on diplomatic relationships between Brazil and the Axis. In a conflict like this, in which mass media was widely used, cinemas were emphasized because, aside of representing an entertainment to people and a good source of income, it was a great source of propaganda; therefore, the seventh art represented to Americans a war weapon on the combat against Nazi regime. In Sergipe, the State that experienced the effects of the battle after the bomb attack by German submarine U-507 to national merchant ships, these films represented, besides an entertainment, a way to know Nazi enemy. Local newspapers were committed to announce the exhibition of these movies in Sergipe’s capital, always searching for a positive publicity. With that said, we used the magazines called Cinearte and A Cena Muda, and the newspapers called Correio de Aracaju, Sergipe Jornal, Folha da Manhã and A Cruzada as sources to develop this academic work, divided into three parts. Besides that, we used some works of VALIM (2013) as a reference, in which he explains the connection between cinema and mass media; and also some works of DE LUCA (2010), in which he explains the use of newspapers as historical sources. That way, it was possible to conclude that there was an effort from Sergipe’s Anti-Nazi newspapers to announce the movies in a way that shared a positive publicity.